Single-use flexible ureteroscopes: Comparative in vitro analysis of four scopes - Abhijit Patil; Shashank Agrawal; Rohan Batra; Abhishek Singh; Arvind Ganpule; Ravindra Sabnis; Mahesh Desai (Asian Journal of Urology, 2023)
Objective: Single-use flexible ureteroscopes (fURSs) have recently been introduced by different companies. Goal of this in-vitro study was to compare four fURSs. Methods: We performed in vitro analysis of Uscope 7.5 Fr and Uscope 9.5 Fr (Pusen Ltd., Zhuhai, China), LithoVue 9.5 Fr (LithoVue™, Boston Scientific, MA, USA), and Indoscope 9.5 Fr (Bioradmedisys™, Pune, India). Optical characteristics (image resolution, color representation, and luminosity) were compared at various distances of 10 mm, 20 mm, and 50 mm. Deflection and irrigation were evaluated with and without accessories. Results: Color perception was comparable for all scopes at 10 mm (p<0.05), while Lithovue 9.5 Fr was comparable with Indoscope 9.5 Fr at the distances of 20 mm and 50 mm. Both scopes were statistically better than both Uscopes at the distances of 20 mm and 50 mm. Image resolution powers were comparable amongst all fURSs at the distances of 10 mm and 20 mm (3.56 line pairs per millimeter [lp/mm]). However, Indoscope (3.56 lp/mm) was superior to LithoVue and Uscope scopes (3.17 lp/mm) at the distance of 50 mm. Luminosity at the distance of 10 mm was comparable for LithoVue and Uscope 9.5 Fr. However, at the distances of 20 mm and 50 mm, LithoVue had the highest luminosity while Uscope 7.5 Fr had the lowest one. Indoscope had lower luminosity than other 9.5 Fr scopes at all distances. With empty working channel and 200 μm laser fiber, Indoscope had the maximum deflection (285°). With basket, Uscope 7.5 Fr had the maximum loss of deflection (30°) while Indoscope had no deflection loss. With empty working channel, all scopes had comparable irrigation flow rates in both deflected and undeflected state. Similarly, with 200 μm laser or basket, irrigation flow rates were comparable in all scopes. Conclusion: Color representation was equivalent for Indoscope and LithoVue, while being better than Uscope 7.5 Fr and Uscope 9.5 Fr. Image resolution was comparable in all scopes at the distances of 10 mm and 20 mm. Beyond the distance of 10 mm, luminosity of LithoVue was the highest and that of Uscope 7.5 Fr was the lowest. Deflection loss was the minimum with Indoscope and the maximum with 7.5 Fr Uscope. Under all scenarios, irrigation flow rates were comparable in all scopes.